Perancangan Aplikasi Diagnosis dan Pemetaan 10 Penyakit Berbasis Android Pada Teaching Factory Nutrition Care Center - Erna Selviyanti; Mochammad Choirur Roziqin; Dony Setiawan Hendyca Putra (Puslitbang Sinergis Asa Professional, 2023)
There has been an increase in non-communicable diseases in Indonesia in terms of morbidity and mortality. One of the risk factors for non-communicable diseases is obesity, high blood sugar and malnutrition in children. The need for public awareness and knowledge regarding the disease they have, because the increase in non-communicable diseases can cause a decrease in the activity of human resources in Indonesia and affect the quality of life. Usually non-communicable diseases are experienced by the elderly, but now they are starting to threaten the productive age group from 10 to 14 years old. Politeknik Negeri Jember has a TeFa NCC which is a Nutrition Service Center. TeFa NCC is intended for the community to carry out health consultations. In carrying out a health consultation, the patient is given a health record in the form of paper (manual) which the patient can take home. This sometimes makes it difficult for health cadres to see the track record of changes in a patient's health if the patient does not bring a consultation paper when he comes for a follow-up consultation. Proposed a design media design application for Diagnosing and Mapping 10 Android-Based Diseases in the Teaching Factory Nutrition Care Center. This application design is intended for the development of applications that can perform early diagnosis of the top 10 diseases in TeFa NCC. The method used in designing the application design is to use the waterfall model. The application design is designed for Android-based mobile devices. There is a splash screen menu, login menu, main display menu, patient data menu, added patient data menu, profile menu, most disease information menu, filtering, distribution map and diagnosis added menu. The designed design is based on the needs and requirements of the user. The design of the application design was successfully carried out